2015
DOI: 10.1186/s12891-015-0571-9
|View full text |Cite
|
Sign up to set email alerts
|

Leg-length discrepancy is associated with low back pain among those who must stand while working

Abstract: BackgroundSome studies suggest that leg length discrepancy (LLD) is associated with low back pain (LBP) but many have not found such an association leading to conflicting evidence on the role of LLD in LBP.MethodsThe study population consisted of meat cutters with a standing job and customer service workers with a sedentary job from Atria Suomi Ltd (Nurmo, Finland) who were at least 35 years old and had been working in their jobs for at least 10 years. Leg length of each participant was measured with a laser r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…However, several articles have reported concerns that a leg-length discrepancy of 5 to 10 mm is associated with lower back pain and gait abnormalities. [10][11][12][13] Therefore, the magnitude of leglength change after OW HTO was sufficiently large to cause clinical symptoms such as lower back pain and gait abnormalities, whereas it was negligible after CW HTO. OW and CW HTOs are most widely used for treating medial compartmental osteoarthritis of the knee with varus deformity, and each method has its own advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several articles have reported concerns that a leg-length discrepancy of 5 to 10 mm is associated with lower back pain and gait abnormalities. [10][11][12][13] Therefore, the magnitude of leglength change after OW HTO was sufficiently large to cause clinical symptoms such as lower back pain and gait abnormalities, whereas it was negligible after CW HTO. OW and CW HTOs are most widely used for treating medial compartmental osteoarthritis of the knee with varus deformity, and each method has its own advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been concerns about complications such as lower back pain and gait abnormalities related to a leg-length discrepancy of >5 mm. 10,11 Rannisto et al 11 reported that patients with leg-length discrepancies >6 mm presented with more severe and frequent lower back pain than patients with no leg-length discrepancies. Bae et al 6 reported that 57% (17 of 30) of patients showed a >6-mm change in leg length after OW HTO, whereas none showed such a change after CW HTO.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, if a pre-existing asymptomatic leg length discrepancy is present, even a small change may lead to symptomatic complications. Rannisto et al 25 reported that patients who must stand while working and who had leg length discrepancies of >6 mm presented with a higher degree of lower back pain and more days with lower back pain than patients with no leg length discrepancies. In addition, Walsh et al 26 performed a gait analysis study and reported that various compensatory mechanisms, such as pelvic obliquity or flexion of the knee of the longer leg, occurred in patients who had >10 mm discrepancy in leg length.…”
Section: Discussionmentioning
confidence: 99%
“…Th e results showed no association between injury and LLD. Th e association between LBP and LLD was confi rmed by Rannisto et al (2015) involving meat cutters and service workers on their study. Th e results showed LBP was obviously correlated with LLD.…”
Section: Discussionmentioning
confidence: 86%